Effects of strength training on blood pressure and heart rate variability - a systematic review - Corso, M.; de Figueiredo, T.; Carvalho, D.; Brown, A.; de Salles, B.; Simão, R.; Willardson, J. M.; Dias, I. (Strength and Conditioning Journal, 2022)
Strength training (ST) has been studied for acute and chronic effects on blood pressure (BP) and heart rate variability (HRV). These effects have never been reviewed collectively concerning the variables that comprise a ST program. Therefore, this review aims to examine the manipulation of ST variables (i.e., load intensity, number of sets and repetitions, exercise order, and rest interval length) on BP and HRV after a session and a long-term program. The BP reduced significantly after an ST session independently of the load intensity, the number of sets and repetitions, the rest interval length, the mode, and the participant characteristic (healthy patients or patients with chronic disease). However, a high number of sets and repetitions, prioritizing multijoint exercises, with longer rest interval lengths between sets and exercises may potentiate these effects. In the HRV analyses, most of the trials showed a sympathetic predominance after an ST session. Hence, it is reasonable to confirm that central adjustments are responsible to control hemodynamics after an ST session.